Keeping up with the COVID's—Could siRNA‐based antivirals be a part of the answer?. Issue 6 (14th July 2022) - Forgham, Helen; Kakinen, Aleksandr; Qiao, Ruirui; Davis, Thomas P.
Abstract: Coronavirus disease 2019 (COVID‐19) is a highly contagious viral disease caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). This deadly infection has resulted in more than 5.2 million deaths worldwide. The global rollout of COVID‐19 vaccines has without doubt saved countless lives by reducing the severity of symptoms for patients. However, as the virus continues to evolve, there is a risk that the vaccines and antiviral designed to target the infection will no longer be therapeutically viable. Furthermore, there remain fears over both the short and long‐term side effects of repeat exposure to currently available vaccines. In this review, we discuss the pros and cons of the vaccine rollout and promote the idea of a COVID medicinal toolbox made up of different antiviral treatment modalities, and present some of the latest therapeutic strategies that are being explored in this respect to try to combat the COVID‐19 virus and other COVID viruses that are predicted to follow. Lastly, we review current literature on the use of siRNA therapeutics as a way to remain adaptable and in tune with the ever‐evolving mutation rate of the COVID‐19 virus. Abstract : COVID‐19 is a highly contagious viral disease that has claimed the lives of millions of people worldwide. The virus continues to evolve, and each time it does, there is a greater risk that the vaccines and antivirals initially developed to target this deadly infection will no longer be therapeutically viable. Here we discuss the vaccines and the latest antiviral treatment strategies that are under investigation. In particular, we discuss siRNA and why it could be an important piece of the puzzle in the ongoing fight against COVID‐19.